Kebijakan Kriminal Terhadap Upaya Penanggulangan Tindak Pidana Perdagangan Manusia Dalam Konteks Kejahatan di Bidang Ekonomi - Ibnu Tulaiji Ahmad Al Mugoffary (Fakultas Hukum Universitas Mulawarman, 2009)
Human trafficking is a modern/current form of slavery. It practices both at national and international level. The development of information technology (IT), communication, and transformation, brought the consequence to the more sophisticated crime method. Human trafficking has character as an extra ordinary crime, well organised, and transboundary in which it subsequently classified as Transnational Organized Crime (TOC). Based on a consideration that human trafficking is not only regarding human as victim but also could potentially threat the state finance, it has been classified as Economic Crime. In this regard, the criminal policy is very important to be endorsed in order to overcome any kind transnational and international crime which appears in globalisation era.